Critical Kirchhoff-Choquard system involving the fractional p-Laplacian operator and singular nonlinearities - Sang, Yanbin (Topological Methods in Nonlinear Analysis, 2021)
In this paper we study a class of critical fractional p-Laplacian Kirchhoff-Choquard systems with singular nonlinearities and two parameters λ and μ. By discussing the Nehari manifold structure and fibering maps analysis, we establish the existence of two positive solutions for above systems when λ and μ satisfy suitable conditions.